Advanced Underground Space Technology - Gong, Chenjie; Lei, Mingfeng; Shen, Xianda (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The recent development of underground space technology makes underground space a potential and feasible solution to climate change, energy shortages, the growing population, and the demands on urban space. Advances in material science, information technology, and computer science incorporating traditional geotechnical engineering have been extensively applied to sustainable and resilient underground space applications. The aim of this Special Issue, entitled "Advanced Underground Space Technology", is to gather original fundamental and applied research related to the design, construction, and maintenance of underground space.